Bulbophyllum paramjitii (Orchidaceae: Epidendroideae: Malaxideae): a new species from Sikkim Himalaya, India - Agrawala, Dinesh K.; Sharief, Mohamed U.; Singh, Basant K. (Phytotaxa, 2016)
Bulbophyllum Petit-Thouars (1822) is one of the largest orchid genera with about 2200 taxa, widely distributed in the tropics (Vermeulen 2014). The main centres of diversity are Asia-Pacific (1700 species), Madagascar (200 species) and New Guinea (600 species). Based on evidence from morphological and molecular data, Vermeulen (2014) recommended a wider circumscription of Bulbophyllum.